Institutional Dimensions in Open Government Data : A Deep Dive Into Indonesia’s Satu Data Initiative and Its Implications for Developing Countries - Bernot, Ausma; Tjondronegoro, Dian; Rifai, Bahtiar; Hasan, Rakibul; Liew, Alan Wee-Chung; Verhelst, Tom; Tiwari, Milind (Taylor & Francis, 2024)
Institutional factors such as data standardization, data interoperability, and the ability to include other stakeholders (e.g., civil society) in ecosystems are now understood as crucial considerations in Open Government Data (OGD) implementation. However, most of the current understanding of institutional factors linked to OGD growth has evolved around highly digitalized and developed countries. This study aims to address this gap by investigating open data implementation in Indonesia, a developing country that has been an early advocate of OGD in the "Asia Pacific". In 2014, Indonesia implemented Satu Data Indonesia (One Data Indonesia) as a national initiative to promote OGD objectives. We employ institutional dimensions as the central theoretical lens to unpack the successes and impediments to Satu Data Indonesia’s development. This research dataset is built on 16 expert interviews from government (n = 14) and private (n = 2) organizations that directly contribute to the growth of Satu Data Indonesia, qualitatively triangulated with documentary analysis of key policy and regulatory documents. These new data provide important insights into the complexity and challenges of nationwide OGD implementation and data-sharing. Our findings show that despite its being an early advocate, Indonesia’s OGD initiative is still in the early stages of development, impeded by several policy and administrative bottlenecks.
Keywords: Institutional dimensions; Open Government Data; Satu Data Indonesia; fi=Kansainvälinen liiketoiminta|en=International Business|